Characterization of Fe-N nanocrystals and nitrogen–containing inclusions in (Ga,Fe)N thin films using transmission electron microscopy - Kovács, A. (2013)
Nanometric inclusions filled with nitrogen, located adjacent to FenN (n ¼ 3 or 4) nanocrystals within (Ga,Fe)N layers, are identified and characterized using scanning transmission electron microscopy (STEM) and electron energy-loss spectroscopy (EELS). High-resolution STEM images reveal a truncation of the Fe-N nanocrystals at their boundaries with the nitrogen-containing inclusions. A controlled electron beam hole drilling experiment is used to release nitrogen gas from an inclusion in situ in the electron microscope. The density of nitrogen in an individual inclusion is measured to be 1.4 6 0.3 g/cm3 . These observations provide an explanation for the location of surplus nitrogen in the (Ga,Fe)N layers, which is liberated by the nucleation of FenN (n > 1) nanocrystals during growth.